2014
DOI: 10.1111/1574-6941.12364
|View full text |Cite
|
Sign up to set email alerts
|

Identification of toluene degraders in a methanogenic enrichment culture

Abstract: Methanogenic biodegradation involves the cooperative metabolism of syntrophic bacteria that catalyse the initial attack and subsequent degradation of hydrocarbons, and methanogens that convert intermediates such as hydrogen and carbon dioxide, formate, and/or acetate to methane. The identity of syntrophic microbes and the nature of their interactions with other syntrophs and methanogens are not well understood. Furthermore, it is difficult to isolate the organisms responsible for the initial activation and sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 46 publications
1
27
0
Order By: Relevance
“…The high abundance of Firmicutes in TOLDC and NAPDC is consistent with recent reports of anaerobic monoaromatic hydrocarbon-degrading cultures that implicate Firmicutes (for example, Peptococcaceae) as primary hydrocarbon degraders (Abu Laban et al, 2009;Winderl et al, 2010;Sun and Cupples, 2012;Fowler et al, 2014) or playing key roles alongside Deltaproteobacteria (Ficker et al, 1999;Ulrich and Edwards, 2003;Sakai et al, 2009). In contrast, members of the Deltaproteobacteria, particularly Syntrophus/Smithella sp., have been implicated in methanogenic alkane degradation, particularly of longer-chain alkanes (Zengler et al, 1999;Gray et al, 2011;Cheng et al, 2013).…”
Section: Community Compositions Of Methanogenic Hydrocarbon-degradingsupporting
confidence: 88%
“…The high abundance of Firmicutes in TOLDC and NAPDC is consistent with recent reports of anaerobic monoaromatic hydrocarbon-degrading cultures that implicate Firmicutes (for example, Peptococcaceae) as primary hydrocarbon degraders (Abu Laban et al, 2009;Winderl et al, 2010;Sun and Cupples, 2012;Fowler et al, 2014) or playing key roles alongside Deltaproteobacteria (Ficker et al, 1999;Ulrich and Edwards, 2003;Sakai et al, 2009). In contrast, members of the Deltaproteobacteria, particularly Syntrophus/Smithella sp., have been implicated in methanogenic alkane degradation, particularly of longer-chain alkanes (Zengler et al, 1999;Gray et al, 2011;Cheng et al, 2013).…”
Section: Community Compositions Of Methanogenic Hydrocarbon-degradingsupporting
confidence: 88%
“…Additionally, several Peptococcaceae have been identified as primary degraders of BTEX compounds in syntrophic consortia under different electron acceptor conditions, for example for benzene degradation coupled to nitrate reduction [Luo et al, 2014;van der Zaan et al, 2012], sulphate reduction [Herrmann et al, 2010;Taubert et al, 2012] or iron reduction [Kunapuli et al, 2007], or for toluene degradation under methanogenic conditions [Abu Laban et al, 2015;Fowler et al, 2014;Sun et al, 2014b].…”
Section: Anaerobic Degradersmentioning
confidence: 99%
“…Later, Fowler et al [2012] substantiated the placement of this bssA lineage upon catabolic analysis of a methanogenic, toluene-degrading enrichment culture from the Fort Lupton aquifer. Via RT-qPCR, Fowler et al [2014] could even show the active expression of clostridial bssA mRNA in the same microcosms. Similar clostridial bssA sequences affiliated to Desulfosporosinus spp.…”
Section: Catabolic Marker Gene-based Insights Into Degrader Cultures mentioning
confidence: 99%
“…Phylotypes affiliated to Desulfosporosinus assimilated toluene under sulfate-reducing conditions in laboratory microcosms containing tar oil-contaminated sediment [Pilloni et al, 2011;Winderl et al, 2010] or agricultural soil [Sun and Cupples, 2012]. Notably, similar phylotypes assimilated 13 C from labeled toluene also under methanogenic conditions [Abu Laban et al, 2015;Fowler et al, 2014;, indicating the functional versatility of these taxa, being capable of toluene degradation coupled to both sulfate reduction or fermentation. Such functional versatility has been also assumed for anaerobic benzenedegrading Peptococcaceae , as discussed above .…”
Section: Identification Of Anaerobic Toluene Degraders Under Sulfate-mentioning
confidence: 99%
“…A highly enriched methanogenic toluenedegrading culture derived from a gas condensate-contaminated aquifer was examined by RNA-SIP [Fowler et al, 2014], where also a phylotype related to Desulfosporosinus was identified as the key toluene-assimilating organism. Besides the dominant Desulfosporosinus , phylotypes affiliated to several other taxa (Acidobacteria , Actinobacteria , Syntrophaceae , Desulfovibrionales , Chloroflexi) were also shown to assimilate 13 C from labeled toluene to a lesser extent [Fowler et al, 2014;Sun et al, 2014]. This supports the concept of complex syntrophic relationships occurring in methanogenic BTEX degradation.…”
Section: Identification Of Toluene Degraders Under Methanogenic Condimentioning
confidence: 99%